2016
DOI: 10.1002/hrm.21794
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between HR Capabilities and Quality of Patient Care: The Mediating Role of Proactive Work Behaviors

Abstract: Based on theoretical frameworks of resource-based theory, dynamic capabilities, and behavioral perspective on human resource management, we developed a multidimensional construct of human resource (HR) capabilities and tested its relationship with quality of patient care using a national sample of U.S. hospitals. The data on HR capabilities were collected from senior managers (421 individuals nested in 279 hospitals) representing both the administrative and clinical sides of the hospitals. The data on quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…It is suggested that employees who perceive they are managed with positive HRM practices are likely to demonstrate improved performance and competence, which is likely to positively affect organizational outcome . Our review found that CBHRM affects the quality of health care, patient safety, and patient satisfaction . Thus, if we want to drive important organizational outcomes, a good strategy to start with is focusing on “people.”…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that employees who perceive they are managed with positive HRM practices are likely to demonstrate improved performance and competence, which is likely to positively affect organizational outcome . Our review found that CBHRM affects the quality of health care, patient safety, and patient satisfaction . Thus, if we want to drive important organizational outcomes, a good strategy to start with is focusing on “people.”…”
Section: Resultsmentioning
confidence: 99%
“…Khatri, Gupta, and Varma () suggested HR capabilities consist of three dimensions: (a) a CEO who sets a clear strategy and supports the HR function; (b) a head of HR who understands the business and enacts effective leadership behaviors both within the HR department and across other departments; and (c) the professionalism and competencies of HR staff who carry out key HR activities. Khatri et al (, p. 676) hinted at the association between HR capabilities and system strength in suggesting that “HR capabilities are necessary to create a ‘strong HR system’ and reduce the gap between intended and implemented HR practices and systems,” and although they did not test this assumption, they found that HR capabilities have both a direct and indirect effect (through proactivity) on quality of patient care. Research that integrates the findings from Khatri et al () and of our study would provide invaluable information for future theory development and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Khatri et al (, p. 676) hinted at the association between HR capabilities and system strength in suggesting that “HR capabilities are necessary to create a ‘strong HR system’ and reduce the gap between intended and implemented HR practices and systems,” and although they did not test this assumption, they found that HR capabilities have both a direct and indirect effect (through proactivity) on quality of patient care. Research that integrates the findings from Khatri et al () and of our study would provide invaluable information for future theory development and practice. On a broader level, we welcome research that takes a dynamic capabilities perspective (Teece, Pisano, & Shuen, ) to provide a deeper understanding of how HR can contribute to organizational competitiveness in highly volatile environments.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, this article focuses on hospitals and health care workers. These organizations “(…) are facing critical organizational and management challenges (and) need to pay greater attention to organizational and management issues than in the past” (Khatri, Gupta, & Varma, , p. 673). Survey data was coupled with register data on sickness absence in a large Norwegian health enterprise, focusing on the association between shift work and both long‐term and short‐term sickness absence.…”
Section: Introductionmentioning
confidence: 99%